2018
DOI: 10.1186/s41231-018-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effects of high fat diet or disturbed blood flow on glycocalyx integrity and vascular inflammation

Abstract: Background and aims: Endothelial surface glycocalyx shedding plays a role in endothelial dysfunction and increases vessel wall permeability, which can lead to inflammation and atherogenesis. We sought to elucidate whether a high fat diet (HFD) or disturbed blood flow conditions, both of which are atherogenic risk factors, would contribute more detrimentally to pre-atherosclerotic loss of endothelial glycocalyx integrity and vascular inflammation. Methods: Six to seven w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Additionally, mechanotransducers, such as the endothelial glycocalyx (GCX), have been shown to be degraded in response to ischemiareperfusion (Rubio-Gayosso et al, 2006), which may exacerbate issues of proper mechanotransduction. Impaired mechanotransduction may even contribute to the occurrence of ischemic stroke, as the development of blood vessel plaques, which can rupture and lead to ischemic stroke, are known to occur in areas of disturbed blood flow characterized by altered mechanotransduction and degraded GCX layers (van den Berg et al, 2009;Cancel et al, 2016;Harding et al, 2018;Mitra et al, 2018). It is therefore vital to understand the impact of endothelial mechanotransduction in both stroke pathology and occurrence, which will be addressed later in the review.…”
Section: Ischemic Stroke Ischemic Stroke Pathologymentioning
confidence: 99%
“…Additionally, mechanotransducers, such as the endothelial glycocalyx (GCX), have been shown to be degraded in response to ischemiareperfusion (Rubio-Gayosso et al, 2006), which may exacerbate issues of proper mechanotransduction. Impaired mechanotransduction may even contribute to the occurrence of ischemic stroke, as the development of blood vessel plaques, which can rupture and lead to ischemic stroke, are known to occur in areas of disturbed blood flow characterized by altered mechanotransduction and degraded GCX layers (van den Berg et al, 2009;Cancel et al, 2016;Harding et al, 2018;Mitra et al, 2018). It is therefore vital to understand the impact of endothelial mechanotransduction in both stroke pathology and occurrence, which will be addressed later in the review.…”
Section: Ischemic Stroke Ischemic Stroke Pathologymentioning
confidence: 99%
“…Elevated proinflammatory cytokines production induces increased activity and expression of MMP. Previously conducted experimental studies have found that HFD causes loss of vascular elasticity, primarily due to deposition of harmful substances in the walls of blood vessels, which in turn leads to reduction of blood flow ( Declèves et al, 2013 ; Mitra et al, 2018 ; Yuan et al, 2019 ). Since MMPs are one of the factors causing the occlusion as well as damage of blood vessels and periodontal tissue, MMP-2, MMP-9, and TIMP-2 expression was measured in periodontal mice tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance in local vascular flow is in correlation with inhibition of tissue oxygenation and reduction of microvascular blood flow. Disorder of blood flow activity is noted to be an early marker for progression of microvascular pathology ( Clough et al, 2017 ; Mitra et al, 2018 ; Ohsugi et al, 2019 ). HFD contributes to endothelial dysfunction and loss of integrity ( Clough et al, 2017 ; Mitra et al, 2018 ; Münch et al, 2019 ) it has been shown that 2h after a fatty meal, HFD causes endothelial damage by vascular occlusion and leads to decreased blood flow ( Bui et al, 2010 ; Münch et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the carotid arteries of Apoe −/− mice that received no surgical manipulation, the ligated vessels of both strains showed more lipid deposition in the arterial wall (Figures 1 and 4). A recent study has shown that endothelial glycocalyx integrity of partially ligated carotid artery of B6-Apoe −/− mice is compromised more by disturbed blood flow than by exposure to a Western diet (Mitra et al, 2018). Increased endothelial permeability would result in more ApoB-containing lipoprotein accumulation in the walls of ligated arteries (Brown et al, 2004).…”
Section: Atherosclerosis In Contralateral Control Carotid Arterymentioning
confidence: 99%